Method for preparing ice crack-shaped flexible transparent electrode based on silicon substrate and application
By applying a hydrophobic solution on the silicon-based substrate and applying a one-dimensional metal nanomaterial solution to form an ice crack-like conductive network, and adding a polymer substrate, the problems of poor stability and uneven square resistance are solved, and a high stability and uniform square resistance are achieved. It is suitable for flexible electronic devices.
Patent Information
- Application Number
- CN202411461251.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-10-18
AI Technical Summary
When using silicon substrates and one-dimensional metal nanomaterials to prepare ice crack-like flexible transparent electrodes, there are problems of poor stability and uneven square resistance, and the droplets cannot be effectively pinned, making it difficult to form ice crack-like conductive electrodes.
By uniformly applying the hydrophobic solution to the surface of the silicon-based substrate and applying a one-dimensional metal nanomaterial solution vertically, an ice-crack-like conductive network is formed, followed by coating the liquid polymer substrate and curing, and finally peeling off to obtain an ice-crack-like flexible transparent electrode.
It achieves uniform square resistance, low surface roughness and high stability of ice crack-like flexible transparent electrodes. It is suitable for flexible electronic devices and has excellent photoelectric properties.
Smart Images

Figure CN119694659A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of conductive electrodes, and in particular relates to a method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate and an application thereof. Background Art
[0002] The statements in this section merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] Flexible transparent electrodes (FTEs) have high transmittance, low sheet resistance and good mechanical flexibility, and are widely used in various electronic devices (such as electric heaters, electromagnetic shielding films, wearable sensors, etc.). Among them, the performance of ice-crack-shaped flexible transparent electrodes (including photoelectric performance, electrothermal stability, chemical stability, mechanical stability, etc.) is much better than that of flexible transparent electrodes with randomly arranged one-dimensional metal nanomaterials. Although the advantage of preparing flexible transparent electrodes on silicon substrates is that the surface of the silicon substrate is extremely smooth and flat; and one-dimensional metal nanomaterials are a new type of flexible transparent conductive material that can achieve efficient charge transfer and excellent conductivity.
[0004] However, the inventors found that there are the following technical difficulties in using silicon substrates and one-dimensional metal nanomaterials to prepare ice crack-shaped flexible transparent electrodes:
[0005] (1) One-dimensional metal nanomaterial conductive electrodes have problems of poor stability and non-uniform sheet resistance in practical applications;
[0006] (2) The pure water contact angle of the silicon substrate is 38.5°. When the one-dimensional metal nanomaterial solution is applied to the silicon substrate by drip coating, scraping or spraying, the droplets cannot be pinned due to the small contact angle, making it difficult to form an ice crack-like conductive electrode. Summary of the invention
[0007] In order to solve the technical problems existing in the above-mentioned background technology, the present invention provides a method and application of preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate, wherein the process of preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate is simple, and the prepared ice crack-shaped flexible transparent electrode has uniform square resistance, low surface roughness and high stability.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] The first aspect of the present invention provides a method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate.
[0010] In one or more embodiments, a method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate includes:
[0011] The hydrophobic solution is evenly applied on the surface of the silicon-based substrate;
[0012] A one-dimensional metal nanomaterial solution with a concentration range of 0.1 mg / ml-10 mg / ml, a diameter range of 10-200 nm, and a length range of 1-500 um is vertically applied to the surface of the silicon-based substrate coated with a hydrophobic solution, and the one-dimensional metal nanomaterial solution is evaporated to form an ice crack-like conductive network;
[0013] coating a liquid high molecular polymer substrate on the ice crack-shaped conductive network, and allowing the liquid high molecular polymer substrate to solidify into a flexible conductive film;
[0014] The flexible conductive film and the silicon substrate are peeled off to obtain an ice crack-shaped flexible transparent electrode.
[0015] Among them, when the concentration of the one-dimensional metal nanomaterial solution is too high, it is equivalent to that each droplet contains more silver nanowires, and the capillary force required to drive the silver nanowires to form ice crack-like conductive electrodes is greater. Beyond a certain range, the capillary force cannot drive the silver nanowires to form ice crack-like conductive electrodes. Through experiments, it is found that the maximum concentration is 10mg / ml. When the concentration is too low, it has no effect on the formation of ice crack-like conductive electrode structure, but because the concentration is too low, the amount of silver nanowires contained in the droplet is too small, so the number of applications required to form ice crack-like conductive electrodes is too many, and the efficiency is low. Through experiments, the lower limit of the concentration is 0.1mg / ml.
[0016] When the length and diameter of the silver nanowire are larger, the weight of a single nanowire is heavier. The ice crack structure of the silver nanowire is driven by the capillary force generated by the evaporation of the solvent. When the silver nanowire is thicker and longer, the required driving force is stronger. When the driving force exceeds the limit value that the solvent volatilization can provide, the ice crack structure cannot be formed. When the length and diameter of the silver nanowire are smaller, the weight of a single nanowire is lighter, the capillary force required is smaller, and the volatility of the solvent is correspondingly lower. However, if the nanowire is too short, more nanowires are required to complete the same size of flexible electrodes, which will increase the intersection of nanowires per unit area, and the intersection is prone to cause high junction resistance and electrothermal instability.
[0017] As an implementation mode of the first aspect of the present invention, the hydrophobic solution is at least one of Arcelor invisible waterproofing agent and SINWE electronic nano waterproof coating.
[0018] The advantage of the above technical solution is that the Arcelor invisible waterproofing agent and SINWE electronic nano waterproof coating, both of these hydrophobic solutions contain esters and lipids. Lipids are incompatible with water, so they can increase the contact angle. At the same time, the hydrophobic solution has a certain viscosity, which can hinder the movement of droplets and ensure that the droplets can be pinned on the surface of the droplets, which is conducive to the formation of ice crack structure.
[0019] As an implementation of the first aspect of the present invention, the hydrophobic solution is applied to the surface of the silicon-based substrate at least twice until the hydrophobic solution on the surface of the silicon-based substrate is uniform.
[0020] The advantage of the above technical solution is that the effective components of the hydrophobic solution are mainly lipids and esters. If it is not applied evenly, ice crack-shaped conductive electrodes can be formed in some areas, but the overall conductive electrode resistance is uneven, which affects its conductivity and stability. When the conductive electrode has an uneven resistance, the current in the area with lower resistance is large after power is turned on, which is easy to generate more Joule heat and cause overheating and damage to the electrode. After applying the hydrophobic solution for the first time, some areas will be uneven. By applying the hydrophobic solution for the second time, the hydrophobic layer on the entire surface is uniform and of equal thickness, and the corresponding overall ice crack-shaped conductive electrode resistance is more uniform.
[0021] As an implementation of the first aspect of the present invention, the thickness of the silicon-based substrate is 100 μm-1 cm and the area is 0.1 cm 2 -50cm 2 .
[0022] The advantage of the above technical solution is that the silicon-based substrate is used to provide a surface with certain tension and low surface energy for the formation of the ice crack-like structure of the one-dimensional metal nanomaterial.
[0023] As an implementation mode of the first aspect of the present invention, a one-dimensional metal nanomaterial solution is sprayed on the surface of a silicon-based substrate coated with a hydrophobic solution using a spray gun, the nozzle diameter of the spray gun is 0.1-10 mm, the nozzle is 1-100 cm away from the silicon substrate, and the carrier gas is an inert gas.
[0024] The advantage of the above technical solution is that the size of the ice crack structure can be adjusted by the pressure of the carrier gas, the nozzle size, and the viscosity of the fluid. The higher the carrier gas pressure and the smaller the nozzle size, the easier it is to disperse the one-dimensional metal nanomaterial solution into small droplets, so that these small droplets are sprayed onto the substrate, and the ice crack size obtained after the solvent evaporates and dries will be smaller; similarly, when the concentration of the one-dimensional metal nanomaterial solution is low, that is, the viscosity of the fluid is low, the carrier gas is more likely to disperse the solution into small droplets, resulting in a smaller ice crack structure.
[0025] As an implementation of the first aspect of the present invention, a liquid high molecular polymer substrate is coated on the ice crack-shaped conductive network by spin coating.
[0026] The advantage of the above technical solution is that the thickness of the flexible substrate and the ice-crack-shaped flexible transparent electrode can be easily adjusted by the spin coating method.
[0027] As an implementation of the first aspect of the present invention, the thickness of the coated liquid high polymer substrate is 10-1000 μm.
[0028] The advantage of the above technical solution is that the thickness can ensure the optical stability of the ice crack-shaped flexible transparent electrode.
[0029] As an implementation of the first aspect of the present invention, the liquid polymer substrate is cured by heating, the curing heating temperature is 60-350° C., and the heating time is 20-120 min.
[0030] The advantage of the above technical solution is that by controlling the heating temperature and time, the solvent in the liquid polymer substrate is dried, and because the molecular chains inside the high-temperature polymer change, the molecular chains are more closely connected, and finally a polymer film is formed, thereby improving the optical stability of the ice crack-shaped flexible transparent electrode.
[0031] The second aspect of the present invention provides an application of a method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate.
[0032] In one or more embodiments, an ice crack-shaped flexible transparent electrode prepared by the method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate as described above is applied in electronic devices.
[0033] The beneficial effects of the present invention are:
[0034] (1) The present invention utilizes a silicon substrate and a one-dimensional metal nanomaterial to prepare an ice crack-shaped flexible transparent electrode, which comprehensively utilizes the flatness of the silicon substrate and the high conductivity and transmittance of the one-dimensional metal nanomaterial. The ice crack-shaped conductive network obtained in the preparation process has a more uniform square resistance distribution and a lower surface roughness than the conductive network formed by the random arrangement of the one-dimensional metal nanomaterial, which can make it more stably used in flexible electronic devices; and the one-dimensional metal nanomaterial has high conductivity and transmittance, and the polymer substrate material also has excellent transmittance, so the flexible transparent electrode finally prepared has excellent photoelectric properties.
[0035] (2) In the process of preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate, the present invention uniformly applies a hydrophobic solution on the surface of the silicon-based substrate. This can increase the contact angle to 100.3° without affecting the substrate structure, thereby increasing the contact angle. When a one-dimensional metal nanomaterial solution is applied to the substrate, the solution can be pinned on the substrate. At the same time, as the solvent in the solution evaporates, the solvent evaporation rate at the edge of the solution is greater than that in the middle of the solution, which will generate a capillary force toward the edge. The capillary force is much greater than the Marangoni reflux toward the middle of the solution caused by the surface tension gradient, thereby driving the one-dimensional metal nanomaterial to be deposited at the edge of the droplet, and finally preparing a conductive electrode with a one-dimensional metal nanomaterial arrangement structure similar to an ice crack.
[0036] (3) The process of preparing the ice crack-shaped flexible transparent electrode based on the silicon substrate of the present invention is simple and can be prepared on a large area so that it can be used for industrial production. In addition, the size of the ice crack-shaped conductive network can be easily adjusted by adjusting the parameters of spraying, dripping and scraping, thereby improving the conductive performance according to the application purpose.
[0037] (4) The ice crack-like conductive network of the present invention has large-sized knots and bundles, has lower surface energy, and therefore has higher stability. It can be applied to electronic equipment working in extreme environments, such as aerospace and metallurgical equipment in high-temperature working environments, or chemical equipment containing chemical corrosion. It has significant advantages over the conductive film materials in the prior art.
[0038] Advantages of additional aspects of the present invention will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0040] Figure 1 This is a schematic flow chart of a method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate provided by the present invention;
[0041] Figure 2 is an optical microscope image of the silicon-based ice crack-like conductive network of Example 1 of the present invention;
[0042] Figure 3 This is an atomic force microscope test spectrum of the flexible transparent electrode of Example 1 of the present invention;
[0043] Figure 4 This is a test graph of electrical and thermal stability of the flexible transparent electrode of Example 1 of the present invention;
[0044] Figure 5 is a graph of the uniformity of square resistance of the flexible transparent electrode of Example 2 of the present invention;
[0045] Figure 6 is a performance diagram of an electric heater based on a flexible transparent electrode according to Example 3 of the present invention;
[0046] Figure 7 It is an optical microscope image of the conductive network on the surface of the glass substrate of Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0047] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0048] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0049] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0050] Terminology explanation:
[0051] Ice crack-like structure: When a one-dimensional metal nanomaterial solution of a certain concentration is deposited on a substrate by spraying, dripping or scraping, the evaporation rate in the middle of the droplet is lower than that in the edge area. The capillary flow generated in this way will inhibit the Malegonzi effect, causing the one-dimensional metal nanomaterial in the solution to be driven from the center position to the edge position, producing an "ice crack-like structure". The "ice crack-like structure" mentioned in this application document refers to a continuous ring structure formed by the one-dimensional metal nanomaterial on the surface of the substrate material.
[0052] Silicon-based substrate: n-type silicon wafer or p-type silicon wafer.
[0053] Figure 1 The present invention provides a method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate. Figure 1 As shown, a method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate according to an embodiment of the present invention comprises:
[0054] Step 1: Apply the hydrophobic solution evenly on the surface of the silicon-based substrate;
[0055] Step 2: vertically apply a one-dimensional metal nanomaterial solution with a concentration range of 0.1 mg / ml-10 mg / ml, a diameter range of 10-200 nm, and a length range of 1-500 um to the surface of the silicon-based substrate coated with a hydrophobic solution, and wait for the one-dimensional metal nanomaterial solution to evaporate to form an ice crack-like conductive network;
[0056] Step 3: coating a liquid polymer substrate on the ice crack-shaped conductive network, and waiting for the liquid polymer substrate to solidify into a flexible conductive film;
[0057] Step 4: Peel off the flexible conductive film and the silicon substrate to obtain an ice crack-shaped flexible transparent electrode.
[0058] This embodiment uses a silicon substrate and a one-dimensional metal nanomaterial to prepare an ice crack-shaped flexible transparent electrode, which comprehensively utilizes the flatness of the silicon substrate and the high conductivity and transmittance of the one-dimensional metal nanomaterial. The ice crack-shaped conductive network obtained in the preparation process has a more uniform square resistance distribution and a lower surface roughness than the conductive network formed by the random arrangement of the one-dimensional metal nanomaterial, which can make it more stably used in flexible electronic devices; and the one-dimensional metal nanomaterial has high conductivity and transmittance, and the polymer substrate material also has excellent transmittance, so the flexible transparent electrode finally prepared has excellent photoelectric properties.
[0059] In step 1, the silicon-based substrate is an n-type silicon substrate or a p-type silicon substrate.
[0060] In one or more embodiments, the silicon-based substrate has a thickness of 100 μm-1 cm and an area of 0.1 cm 2 -50cm 2 Among them, the silicon-based substrate is used to provide a surface with certain tension and low surface energy for the formation of ice crack-like structures of one-dimensional metal nanomaterials.
[0061] The hydrophobic solution in step 1 can be prepared specifically according to actual conditions and will not be described in detail here.
[0062] In step 1, the hydrophobic solution is evenly applied to the surface of the silicon-based substrate, which does not affect the substrate structure and can increase the contact angle to 100.3°, making the contact angle larger. When the one-dimensional metal nanomaterial solution is applied to the substrate, the solution can be pinned on the substrate. At the same time, as the solvent in the solution evaporates, the solvent evaporation rate at the edge of the solution is greater than that in the middle of the solution, which will generate a capillary force toward the edge. The capillary force is much larger than the Marangoni reflux toward the middle of the solution caused by the surface tension gradient, thereby driving the one-dimensional metal nanomaterial to be deposited at the edge of the droplet, and finally preparing a conductive electrode with an ice crack-like structure of a one-dimensional metal nanomaterial arrangement.
[0063] In step 2, the one-dimensional metal nanomaterial solution includes but is not limited to silver nanowires, copper nanowires and gold nanowires. Different types of metal nanowires have different lengths and diameters, especially conventional silver nanowires have larger diameters and longer lengths, and the corresponding nanowires have greater mass. Conventional parameters make it difficult to drive the nanowires and form ice-crack-shaped flexible transparent electrodes, so it is necessary to increase the air pressure and enhance the capillary force so that the nanowires can be deposited to form ice-crack-shaped electrodes.
[0064] As a preferred embodiment, the concentration of the one-dimensional metal nanomaterial solution is 0.001-10 mg / ml. The ice crack-like conductive network formed by the one-dimensional metal nanomaterial solution within this concentration range has high stability.
[0065] In step 2, the one-dimensional metal nanomaterial is applied by methods including but not limited to spraying, dripping or scraping.
[0066] Preferably, a one-dimensional metal nanomaterial solution with a concentration range of 0.1mg / ml-10mg / ml, a diameter range of 10-200nm, and a length range of 1-500um is applied vertically to the surface of the silicon-based substrate after the hydrophobic solution by spraying; wherein the normal line of the one-dimensional metal nanomaterial solution column during the spraying process is perpendicular to the surface of the silicon-based substrate. This ensures the formation of an ice crack-shaped flexible transparent electrode with uniform square resistance.
[0067] For example, a one-dimensional metal nanomaterial solution is sprayed on the surface of a silicon-based substrate coated with a hydrophobic solution using a spray gun, the diameter of the nozzle of the spray gun is 0.1-10 mm, the distance from the nozzle to the silicon substrate is 1-100 cm, and the carrier gas is an inert gas, wherein the inert gas includes but is not limited to high-purity air, nitrogen, argon, etc.
[0068] The size of the ice crack structure can be adjusted by the pressure of the carrier gas, the nozzle size, and the viscosity of the fluid. The higher the carrier gas pressure and the smaller the nozzle size, the easier it is to disperse the one-dimensional metal nanomaterial solution into small droplets, so that these small droplets are sprayed onto the substrate, and the size of the ice crack obtained after the solvent evaporates and dries will be smaller; similarly, when the concentration of the one-dimensional metal nanomaterial solution is low, that is, the viscosity of the fluid is low, the carrier gas is more likely to disperse the solution into small droplets, resulting in a smaller ice crack structure.
[0069] In addition, spraying requires the volatility of the solvent. The faster the solvent evaporates, the greater the capillary force generated by the volatilization, and the more it can drive the silver nanowires to deposit at the edge of the solution. When the solvent volatility is too strong, the ice crack-shaped conductive electrode formed has disconnected parts. The reason is that the volatility is too high, causing most of the nanowires to be deposited at the intersection of multiple droplets, that is, the intersection of ice cracks. Too low volatility will cause the droplets to not dry, and it is difficult to generate capillary forces to drive the nanowires to deposit at the edge of the droplets. The air pressure during spraying is a factor that affects whether the droplets can dry quickly. The greater the air pressure, the faster the gas flow rate generated during spraying, and the faster the droplets dry. However, excessive air pressure will disperse the silver nanowires, so the air pressure range is 0.01-1Mpa.
[0070] In step 3, a liquid polymer substrate is coated on the ice crack-shaped conductive network by spin coating. The thickness of the flexible substrate and the ice crack-shaped flexible transparent electrode can be easily adjusted by spin coating. For example, the rotation speed of the spin coater is 10-2000 rpm, and the spin coating time is 1-200 s.
[0071] Among them, the polymer substrate includes but is not limited to colorless polyimide (CPI) film, polyimide (PI) film, polyester (PET) film, polydimethylsiloxane (PDMS) film, styrene rubber (SEBS) film, polytetrafluoroethylene (PTFE) film, polyvinyl chloride (PVC) film, etc.
[0072] When the high molecular polymer substrate is a colorless polyimide film, it has good chemical stability, electrical stability and thermal stability, and has excellent optical properties, which will improve the service life and stability of the device and the optoelectronic properties.
[0073] The thickness of the coated liquid polymer substrate is 10-1000 μm. This thickness can ensure the optical stability of the ice crack-shaped flexible transparent electrode. Those skilled in the art can select a suitable thickness according to the purpose of use. When the thickness is large, it can be achieved by multiple coatings.
[0074] The solid content of the liquid colorless polyimide flexible substrate is 5-50%.
[0075] For example, the liquid polymer substrate is cured by heating, the curing heating temperature is 60-350°C, and the heating time is 20-120 minutes. In this way, the solvent in the liquid polymer substrate is dried by controlling the heating temperature and time, and because the molecular chains inside the high-temperature polymer change, the molecular chains are more closely connected, and finally a polymer film is formed, thereby improving the optical stability of the ice crack-shaped flexible transparent electrode.
[0076] The purpose of coating a liquid polymer substrate is to wrap a one-dimensional metal nanomaterial. After the one-dimensional metal nanomaterial is applied to the silicon substrate, the adhesion to the silicon substrate is weak, and the one-dimensional metal nanomaterial is easy to fall off the substrate, so the liquid polymer coating method is adopted. The liquid polymer is dripped onto the surface of the silicon substrate, and then the substrate is rotated by a spin coater. The liquid polymer is evenly spread on the substrate through centrifugal force and covers the one-dimensional metal nanomaterial. The coating is required to be free of bubbles and uniform in thickness.
[0077] In step 4, the thin film can be peeled off from the silicon substrate by the experimenter using tweezers to peel off a corner.
[0078] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0079] Example 1
[0080] In this embodiment, a silicon substrate-based ice crack-shaped flexible transparent electrode is provided, and the preparation method of the electrode is as follows:
[0081] (1) A hydrophobic solution is evenly applied on the surface of a silicon-based substrate, and silver nanowires with a diameter and length of 30 nm and 20 μm, respectively, are selected and added to methanol to prepare a Ag NWs solution with a concentration of 0.5 mg / ml. The Ag NWs solution is added to a spray gun with a nozzle diameter of 0.3 mm and a spray distance of 10 cm. The Ag NWs solution is sprayed on a 3 cm×3 cm n-type silicon substrate, and the square resistance is controlled to be about 30 Ω / sq. The solution is evaporated to form an ice crack-like conductive network.
[0082] (2) The n-type silicon substrate with the ice crack structure formed is placed on a coating machine, and a liquid colorless polyimide solution is spin-coated on the n-type silicon substrate sprayed with the Ag NWs ice crack structure at a rotation speed of 500 rpm.
[0083] (3) The liquid colorless polyimide and the n-type silicon substrate coated with the Ag NWs ice crack structure conductive network are placed in an oven and heated at 100° C. for 60 minutes, and the above structure is cured into a film.
[0084] (4) After the silicon substrate sprayed with the Ag NWs ice crack conductive network and the solidified flexible conductive film are cooled, the CPI layer and the Ag NWs layer are peeled off from the silicon substrate to obtain the flexible transparent electrode.
[0085] In this embodiment, the surface roughness of the conductive film described in Embodiment 1 was tested. Figure 2 It is an optical microscope image of a silicon-based ice crack-like conductive network; Figure 3This is an atomic force microscope test spectrum of the flexible transparent electrode of Example 1 of the present invention. Figure 3 It can be seen that the root mean square roughness RMS of the flexible transparent electrode based on the n-type silicon substrate described in Example 1 is 4.57nm. This is mainly due to the atomic-level roughness of the n-type silicon substrate itself. In addition, its electrothermal stability is also tested. Figure 4 As shown, it can withstand a high temperature of 340°C and a high voltage of 8V without a significant change in square resistance, has excellent electrothermal stability, can be used in harsh environments, and broadens its application range.
[0086] Example 2
[0087] In this embodiment, a silicon substrate-based ice crack-shaped flexible transparent electrode is provided, and the preparation method of the electrode is as follows:
[0088] (1) A hydrophobic solution is evenly applied on the surface of a silicon-based substrate, and silver nanowires with a diameter and length of 10 nm and 20 μm, respectively, are selected and added to IPA to prepare a Ag NWs solution with a concentration of 0.5 mg / ml. The Ag NWs solution is added to a spray gun with a nozzle diameter of 0.3 mm and a spray distance of 15 cm. The Ag NWs solution is sprayed on a 6 cm×6 cm n-type silicon substrate, and the square resistance is controlled to be about 7.5 Ω / sq. The solution is evaporated to form an ice crack-like conductive network.
[0089] (2) The n-type silicon substrate with the ice crack structure formed is placed on a coating machine, and a liquid colorless polyimide solution is spin-coated on the n-type silicon substrate sprayed with the Ag NWs ice crack structure at a rotation speed of 900 rpm.
[0090] (3) placing the liquid colorless polyimide and the n-type silicon substrate coated with the Ag NWs ice crack structure conductive network in an oven and heating them at 120° C. for 30 min to solidify the structure into a film.
[0091] (4) After the silicon substrate sprayed with the Ag NWs ice crack conductive network and the solidified flexible conductive film are cooled, the CPI layer and the Ag NWs layer are peeled off from the silicon substrate to obtain the flexible transparent electrode.
[0092] This embodiment also verifies the electrical performance of the uniformity of the square resistance of the conductive film described in Embodiment 1. Figure 5 As shown, the square resistance uniformity is good, and the maximum square resistance change is about 5%, which is comparable to high-quality ITO / PET.
[0093] Example 3
[0094] In this embodiment, a silicon substrate-based ice crack-shaped flexible transparent electrode is provided, and the preparation method of the electrode is as follows:
[0095] (1) A hydrophobic solution is evenly applied on the surface of a silicon-based substrate, and silver nanowires with a diameter and length of 80 nm and 60 μm, respectively, are selected and added to ethanol to prepare a Ag NWs solution with a concentration of 1 mg / ml. The Ag NWs solution is added to a spray gun with a nozzle diameter of 0.8 mm and a spray distance of 50 cm. The Ag NWs solution is sprayed on a 2 cm×2 cm n-type silicon substrate, and the square resistance is controlled to be about 20 Ω / sq. The solution is evaporated to form an ice crack-like conductive network.
[0096] (2) The n-type silicon substrate with the ice crack structure formed is placed on a coating machine, and a liquid colorless polyimide solution is spin-coated on the n-type silicon substrate sprayed with the Ag NWs ice crack structure at a rotation speed of 800 rpm.
[0097] (3) The liquid colorless polyimide and the n-type silicon substrate coated with the Ag NWs ice crack structure conductive network are placed in an oven and heated at 130° C. for 45 minutes, and the structure is cured into a film.
[0098] (4) After the silicon substrate sprayed with the Ag NWs ice crack conductive network and the solidified flexible conductive film are cooled, the CPI layer and the Ag NWs layer are peeled off from the silicon substrate to obtain the flexible transparent electrode.
[0099] Then, conductive silver paste is applied to both ends of the electrode to increase electrical contact. After curing, a source meter is used to provide a DC voltage on both sides of the electrode to test the performance of the electric heater. Under a specific driving voltage, Joule heat is generated due to the inelastic collision between accelerated electrons and phonons. Steady-state saturation temperature, response / recovery time, and heating stability are several important indicators for evaluating heater performance, such as Figure 6 As shown, the flexible transparent electric heater has good Joule heating performance.
[0100] Comparative Example
[0101] In this comparative example, a transparent electrode prepared on the surface of a glass substrate is provided. As is well known in the art, glass is a silicate non-metallic material formed by melting silicon dioxide and other chemical substances, and has a greater surface tension than the surface of a silicon-based substrate. In this comparative example, glass is used as the substrate material, and the other preparation methods are the same as those in Example 1. The obtained conductive film is as follows Figure 7 As shown, the solidified nanosilver can only be stacked in a linear shape and the "ice crack" structure cannot be obtained, and its conductive performance is significantly reduced.
[0102] During the experiment, we tried many other similar materials or substrate materials with low surface tension, but none of them could achieve the same stable and reproducible effect as silicon-based substrates.
[0103] In one or more embodiments, there is also provided an ice crack-shaped flexible transparent electrode prepared by the method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate as described above, which is applied in electronic devices.
[0104] The electronic devices here can be used in the fields of information, energy, medicine and defense.
[0105] Among them, information applications include but are not limited to the preparation of electronic displays, electronic storage materials, touch materials, printing equipment, etc.
[0106] Applications in the medical field include but are not limited to the preparation of flexible wearable medical devices.
[0107] Applications in the energy field include but are not limited to thin-film solar cells, metallurgical equipment, and heat treatment equipment.
[0108] Defense applications include, but are not limited to, applications in aerospace.
[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate, characterized in that: include: The hydrophobic solution is evenly applied on the surface of the silicon-based substrate; A one-dimensional metal nanomaterial solution with a concentration range of 0.1 mg / ml-10 mg / ml, a diameter range of 10-200 nm, and a length range of 1-500 um is vertically applied to the surface of the silicon-based substrate after the hydrophobic solution is dissolved, and the one-dimensional metal nanomaterial solution is volatilized to form an ice crack-like conductive network; coating a liquid high molecular polymer substrate on the ice crack-shaped conductive network, and allowing the liquid high molecular polymer substrate to solidify into a flexible conductive film; The flexible conductive film and the silicon substrate are peeled off to obtain an ice crack-shaped flexible transparent electrode.
2. The method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate according to claim 1, characterized in that: The hydrophobic solution is at least one of Arcelor invisible waterproofing agent and SINWE electronic nano waterproof coating.
3. The method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate according to claim 1, characterized in that: The hydrophobic solution is applied to the surface of the silicon-based substrate at least twice until the hydrophobic solution on the surface of the silicon-based substrate is uniform.
4. The method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate according to any one of claims 1, characterized in that: The thickness of the silicon-based substrate is 100 μm-1 cm.
5. The method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate according to claim 1, characterized in that: The area of the silicon-based substrate is 0.1 cm 2 -50cm 2 .
6. The method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate according to claim 1, characterized in that: A one-dimensional metal nano material solution is sprayed on the surface of a silicon-based substrate coated with a hydrophobic solution by using a spray gun, the nozzle diameter of the spray gun is 0.1-10 mm, the distance from the nozzle to the silicon substrate is 1-100 cm, and the carrier gas is an inert gas.
7. The method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate according to claim 1, characterized in that: The liquid high molecular polymer substrate is coated on the ice crack-shaped conductive network by a spin coating method.
8. The method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate according to claim 1, characterized in that: The thickness of the coated liquid high molecular polymer substrate is 10-1000 μm.
9. The method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate according to claim 1, characterized in that: The liquid polymer substrate is cured by heating, the curing heating temperature is 60-350°C, and the heating time is 20-120 minutes.
10. An ice crack-shaped flexible transparent electrode prepared by the method for preparing an ice crack-shaped flexible transparent electrode based on a silicon substrate according to any one of claims 1 to 9, characterized in that: Used in electronic equipment.
Citation Information
Patent Citations
Touch screen manufacturing method, touch screen and displaying device
CN106648259A
Fusion method for nanoliter-sized micro droplets in small-scale reaction tube
CN108273454A
Method for preparing coffee-ring conductive film based on silicon substrate and application of coffee-ring conductive film
CN112863766A
Universal preparation method of coffee-ring-shaped metal nanowire conductive electrode
CN113270234A
Flexible touch screen and flexible touch system
CN221595633U